Frankfurter and Green's Labor Injunction - Taussig, F. W.; Frankfurter, Felix; Green, Nothan (Quarterly Journal of Economics, 1930)
Journal Article Frankfurter and Green's Labor Injunction Get access F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 44, Issue 4, August 1930, Pages 680–686, https://doi.org/10.2307/1884029 Published: 01 August 1930